A Research Study on the Radiological State of Building Material and the Risk Assessment - Savidou, A.; Raptis, C.; Kritidis, P. (HNPS Advances in Nuclear Physics, 2020)
The objective of the present study is focused an the assessment of the radiological risk from building materials used in Attica region, Greece. Bricks and concrete com- monly used in Attica region have been studied for both natural radionuclide content and radon exhalation. The high-resolution gamma-ray spectroscopy technique, as well as radon exhalation measurements, have been employed. The technique used for the measurements of the radon exhalation is called "continuous accumulation- counting" method and has been described in detail by the authors in earlier pub- lications. This measurement technique is based on the continuous air flow through a sealed chamber containing the sample and through a scintillation counter (Lucas cell). The counting is continuous as well.